“Force-Feedback” Leveling of massively parallel arrays in polymer pen lithography - Liao, Xing (Nano Lett, 2010)
Polymer pen lithography (PPL) is a recently developed molecular printing technique which can produce features with diameters ranging from 80 nm to >10 μm in a single writing step using massively parallel (>10(7) pens) arrays of pyramidal, elastomeric pens. Leveling these pen arrays with respect to the surface to produce uniform features over large areas remains a considerable challenge. Here, we describe a new method for leveling the pen arrays that utilizes the force between the pen arrays and the surface to achieve leveling with a tilt of less than 0.004°, thereby producing features that vary by only 50 nm over 1 cm.